PRAKTIK TQM, PERSEPSI KUALITAS LAYANAN DAN KEPUASAN PENGUJUNG Suatu Analisis dengan Pendekatan Partial Least Square - Ratnaningrum Ratnaningrum; Muh. Nasron (Benefit: Jurnal Manajemen dan Bisnis, 2013)
The purpose of this study are to confirm wether the dimensions of top management commitment, costumer focus, benchmarking, training, and employee focus can perform TQM practices variables and to analyze the influences of the perceived service quality to costumersatisfaction. The PLS output shows that TQM practices construct is performed by the dimensionsof top management commitment, costumer focus, benchmarking, training, and employee focus.The other finding is that the perceived service quality influences positively to customer satisfaction.